PENGARUH BIOCHAR DAN NPK TERHADAP BEBERAPA SIFAT FISIKA TANAH DAN PERTUMBUHAN SERTA PRODUKSI KENTANG (Solanum tuberosum L.) - Iwan Saputra; Boy Riza Juanda (Jurnal Agrotek Lestari, 2018)
Provision of biochar as a to soil make better either directly or formulated beforehand with other materials such as with a combination of NPK fertilizers is expected to improve soil physical properties. This study aims to determine the effect of biochar application and NPK either single factor or interaction to changes in soil physical properties, as well as the growth and yield of potatoes. Research using randomized block design (RAK), consists of two factors, namely biochar and NPK. Factors biochar consists of four levels, namely; (1) B0 = Biochar doses of 0 tons ha-1, (2) B1 = Biochar dose of 15 ton ha-1, (3) B2 = Biochar dose of 30 tons ha-1, and (4) B3 = Biochar dose of 45 tons ha-1, while NPK consists of three levels, namely; (1) P0 = NPK doses of 0 kg ha-1, (2) P1 = NPK fertilizer dose of 400 kg ha-1, and (3) P2 = NPK fertilizer dose of 800 kg ha-1. Biochar and NPK fertilizers by the interaction of very significant effect on heavy volume, porosity, stability index aggregated, drainage pore fast, pore slow drainage and pore water available soil, plant height ages of 30 and 45 days after planting, the number of tubers per hill, tuber weight per clump, and weight of tuber per plot. The highest value of potato tuber weight per plot found in biochar dose of 30 tons ha-1 with NPK fertilizer dose of 400 kg ha-1 with a yield of potatoes to a maximum of 16.33 kg plot-1. Keywords: biochar, NPK, potato, soil physical properties